Association between diverse obesity indicators and sleep quality in elderly Chinese people: a National Study - Liang, Zhenzhen; Jin, Wei; Huang, Li; Chen, Huajian (Frontiers in Nutrition, 2024)
Background: The association between obesity indicators and sleep quality remains unclear among elderly Chinese people. Therefore, we aimed to assess this association by utilizing data from the Chinese Longitudinal Healthy Longevity Survey (CLHLS).Methods: A total of 10505 participants aged 65 and above from the 2018 CLHLS were included. Calculate body mass index (BMI), waist circumference (WC), waist-to-height ratio (WHtR) and weight-adjusted-waist index (WWI) based on measured weight, height, and waist circumference. Based on BMI values, individuals were classified as underweight (< 18.5 kg/m 2 ), normal weight (18.5-23.9 kg/m 2 ) and overweight or obesity (BMI ≥24 kg/m 2 ). In the survey, sleep quality was rated in a 5-point format ("1 = very good", "2 = good", "3 = fair", "4 = poor" or "5 = very poor"), and we categorized "1" and "2" as good sleep quality and " 3" "4" and "5" as poor sleep quality.Logistic regression models were used to evaluate odds ratios (ORs) and 95% confidence intervals (CIs), with subgroup analysis and restricted-cubic-spline (RCS) conducted.The prevalence of poor sleep quality was 47.06%. There are significant differences in obesity indicators and other factors between the two groups of people with good sleep and poor sleep. After adjusting for potential confounding factors (including demographics, socioeconomic status, lifestyle behaviors, health-related issues and activities of daily living), our analyses revealed significant negative associations of BMI [OR 0.96 (95%CI 0.95-0.98)], WC [OR 0.99 (95%CI 0.98-0.99)] and WHtR [OR 0.18 (95%CI 0.09-0.35)] with poor sleep quality. RCS regression also showed that BMI, WC, WHtR and WWI were all strongly negatively correlated with poor sleep quality.In elderly Chinese people, overweight/obese elderly people may have a better sleep quality compared to elderly people with normal weight, while underweight elderly people are unfavorable for sleep quality.